(untitled) (Journal of Enam Medical College, 2014)
Background: Women with polycystic ovarian syndrome (PCOS) have chronic anovulation and androgen excess not attributable to another cause. The fundamental pathophysiologic defect is unknown. Defects in LH secretion, LH/FSH ratio, amplitude of LH pulsations have been described; but the prevalence of these defects is not still clearly determined. Objective: To review the variable clinical presentations of polycystic ovarian syndrome. Materials and Methods: This observational study was carried out in Combined Military Hospitals of Jessore, Rangpur and Ghatail during November 2008 to June 2013. One hundred patients attending Gynaecology Outpatient Department (GOPD) having at least two of the following criteria hyperandrogenism, chronic oligo- or anovulation and ultrasonographic findings were selected. In all selected women LH and FSH serum levels were determined and LH/FSH ratios were calculated. Body mass index (BMI) was measured and was scored to classify their state of obesity. The collected data were compiled and arranged in tables and were subjected to analysis. Results: Most of the patients (92%) were 2030 years old. Chief complaint of the patients was infertility, either primary (72%) or secondary (28%). Eighty percent women had menstrual irregularities, 30% were hirsute, 71% cases were overweight and 17% were obese. On pelvic ultrasonogram polycystic ovaries were found in 20% cases and 80% had normal ovaries. Thirty percent patients had LH/FSH ratio between 2.12.9, 32% had >3 and it was found normal in 38% of cases. Conclusion: PCOS cannot be diagnosed by a single clinical or laboratory finding. The diagnostic approach should be based largely on history and physical examination. DOI: http://dx.doi.org/10.3329/jemc.v4i3.20944 J Enam Med Col 2014; 4(3): 156-160